Exploring the Effect of Communication Patterns and Transparency on Performance in a Human-Robot Team. (November 2019) - Lakhmani, Shan G.; Wright, Julia L.; Schwartz, Michael R.; Barber, Daniel
Human-robot interaction requires communication, however what form this communication should take to facilitate effective team performance is still undetermined. One notion is that effective human-agent communications can be achieved by combining transparent information-sharing techniques with specific communication patterns. This study examines how transparency and a robot's communication patterns interact to affect human performance in a human-robot teaming task. Participants' performance in a target identification task was affected by the robot's communication pattern. Participants missed identifying more targets when they worked with a bidirectionally communicating robot than when they were working with a unidirectionally communicating one. Furthermore, working with a bidirectionally communicating robot led to fewer correct identifications than working with a unidirectionally communicating robot, but only when the robot provided less transparency information. The implications these findings have for future robot interface designs are discussed.